Legal Responsibility in the Pollution and Environmental Destruction Due to Gold Mining Exploitation in Botak Mountain of Buru Regency - La Ode Angga La Ode Angga; Hasan Suat (Fiat Justisia: Jurnal Ilmu Hukum, 2019)
From the case of environmental destruction and pollution that occurred in Buru Island, Maluku Province, the principle of civil liability or known as “obligation” or “aanspraakelijkheid” can be used for those who need assistance to the community and can be used for the principle of accountability. In the case of environmental destruction and pollution that occurs on Botak Island, Buru Mountain, the miners used mercury and cyanide to process minerals in obtaining gold. Based on Article 87 paragraph (1) UUPPLH, the obligation from this pollution can be qualified for the fulfilment of violation, including (a) committing an unlawful act; (b) The presence of environmental pollution and or damage; (c) cause harm to other people or the environment; and (d) is a responsibility and/or activity. Furthermore, to be able to fulfill the compensation according to civil law, Article 1365 of the Civil Code requires the existence of a onrechtmatigedaad or acts against the law, which contains: (a) the act violates the law; (b) the action is based on mistakes; (c) the consequences of these consequences;           Article 1365 of the Civil Code can indeed protect one's rights because a party has suffered from the actions of others that cause these disadvantages. Therefore, it is assumed that being against the law here outlines the existence of rights and obligations when committing an act, either an error or negligence or also injuring another person, and resulting in arising from other people.